Obestatin (OB), Calprotectin (FCP) and (SIgA) in Patients Infected with Entamoeba Histolytica in Al-Najaf Governorate, Iraq - Raja Jawad Mohamed Al-Saeedi (Journal of Global Pharma Technology, 2020)
The study included the identification of changes in biomarkers to determine the effect of E. histolytica on the level of calabrotectin, obstobestatin and SIgA in patients parasites, 250 patients were collected from AL-Hakeem Hospital in Najaf from (May 2018) to (October 2018), The number of  patients with amoeba was 115(46%), 65(26%) males and 50 (20%). females and compared with a control group of 50 healthy subjects The results showed sig significant increase(p≤ 0.05) in the level of obestatin, calprotectin, SIgA control groub.